2021
DOI: 10.1021/acs.jmedchem.1c00815
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-((3S,4S)-4-(3,4-Difluorophenyl)piperidin-3-yl)-2-fluoro-4-(1-methyl-1H-pyrazol-5-yl)benzamide (Hu7691), a Potent and Selective Akt Inhibitor That Enables Decrease of Cutaneous Toxicity

Abstract: Rash is one of the primary dose-limiting toxicities of Akt (protein kinase B) inhibitors in clinical trials. Here, we demonstrate the inhibition of Akt2 isozyme may be a driver for keratinocyte apoptosis, which promotes us to search for new selective Akt inhibitors with an improved cutaneous safety property. According to our previous research, compound 2 is selected for further optimization for overcoming the disadvantages of compound 1, including high Akt2 inhibition and high toxicity against HaCaT keratinocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The intragastric 53) is an effective and selective AKT1 inhibitor with a 24-fold selectivity for AKT1 over AKT2 (IC 50 = 4.0 nM vs 98 nM). 146 53 showed low toxicity against keratinocytes (HaCaT IC 50 = 15 μM, hERG inhibition: 16% @ 3 μM), promising kinase selectivity, and remarkable in vitro (IC 50 values of 0.68, 2.5, and 15 μM in HGC-27, 786-O, and KHOS cells, respectively) and in vivo (TGI = 70% and 56% in 786-O and KHOS xenograft BALB/c nude mouse model at the dose of 50 mg/kg through intragastric administration) anticancer effects. In view of excellent PK and safety profiles with t 1/2 = 8.7 h and F = 66% in Sprague−Dawley rats achieved through intragastric administration in preclinical assessments, the oral administration of 53 was authorized by the National Medical Products Administration for clinical trial evaluation.…”
Section: Targeting the Pi3k/akt/mtor Signaling Pathway With Atp-compe...mentioning
confidence: 99%
See 1 more Smart Citation
“…The intragastric 53) is an effective and selective AKT1 inhibitor with a 24-fold selectivity for AKT1 over AKT2 (IC 50 = 4.0 nM vs 98 nM). 146 53 showed low toxicity against keratinocytes (HaCaT IC 50 = 15 μM, hERG inhibition: 16% @ 3 μM), promising kinase selectivity, and remarkable in vitro (IC 50 values of 0.68, 2.5, and 15 μM in HGC-27, 786-O, and KHOS cells, respectively) and in vivo (TGI = 70% and 56% in 786-O and KHOS xenograft BALB/c nude mouse model at the dose of 50 mg/kg through intragastric administration) anticancer effects. In view of excellent PK and safety profiles with t 1/2 = 8.7 h and F = 66% in Sprague−Dawley rats achieved through intragastric administration in preclinical assessments, the oral administration of 53 was authorized by the National Medical Products Administration for clinical trial evaluation.…”
Section: Targeting the Pi3k/akt/mtor Signaling Pathway With Atp-compe...mentioning
confidence: 99%
“…In view of excellent PK and safety profiles with t 1/2 = 8.7 h and F = 66% in Sprague−Dawley rats achieved through intragastric administration in preclinical assessments, the oral administration of 53 was authorized by the National Medical Products Administration for clinical trial evaluation. 146 Li and co-workers 147 used a similar conformational restriction strategy on 13 to provide a novel AKT1 inhibitor 54 (IC 50 = 1.3 nM). Compound 54 showed good PK profiles with t 1/2 value of 4.7 h and F value of 52% in Sprague−Dawley rats through oral gavage.…”
Section: Targeting the Pi3k/akt/mtor Signaling Pathway With Atp-compe...mentioning
confidence: 99%
“…Since Akt is one of the driving genes in many cancers, extra attention has been given to the discovery of Akt inhibitors during the past two decades. Currently, Akt inhibitors are mainly divided into allosteric inhibitors (e.g., MK-2206 , ARQ-092 , and TAS-117 ) and ATP-competitive inhibitors (e.g., GDC-0068 , AZD5363 , and GSK2141795 ), which have been evaluated on solid and hematological tumors in many clinical trials (the chemical structures of these Akt inhibitors are shown in Figure ). Among them, the allosteric inhibitor MK-2206 was developed by Merck in 2009 for the treatment of metastatic solid tumors .…”
Section: Introductionmentioning
confidence: 99%
“…AZD5363 , a pan-Akt inhibitor developed by AstraZeneca, prolonged the progression-free survival (HR = 0.58) and OS (HR = 0.59) of the patients with advanced breast cancer when combined with fulvestrant . In 2020, Hu-7691 was optimized to exhibit low human hERG blockade based on the chemical structure of GSK2141795 through a structure-based drug design method, providing methods for advanced ATP-competitive Akt inhibitors. , Notably, GDC-0068 is another Akt inhibitor with a high selectivity profile. In advanced prostate cancer that is resistant to metastatic castration, GDC-0068 (Genentech Inc.) prolonged the median radiographical progression-free survival (HR = 0.77) of patients who had tumors with PTEN loss when combined with abiraterone and prednisolone in a phase III clinical trial (IPATential150), which fully demonstrated the promising prospect of GDC-0068 as an anticancer drug .…”
Section: Introductionmentioning
confidence: 99%
“…Accurate SARs may be obtained by comprehensively comparing side chains without changing the scaffold, which is the central backbone of the original molecule. Some of the latest research to identify anticancer drugs, psychiatric drugs, , antivirus drugs, , and even antibody–drug conjugates , are based on SARs, which represent an indispensable important research method.…”
Section: Introductionmentioning
confidence: 99%